DISCOURSE ANALYSIS OF OPRAH WINFREY'S SPEECH AT 2024 DEMOCRATIC NATIONAL CONVENTION - Saleh, Kawther Adnan; Abed, Hind Mohammed; Fattah, Sahar Abdul-Razzaq (Journal of Social Science, 2026)
Objective: This study elucidates Oprah Winfrey's address at the 2024 Democratic National Convention. It seeks to examine the many forms of lexical and grammatical coherence according to the theory of Halliday and Hasan (1976). Method: The data analysis indicated that the use of both lexical and grammatical cohesion significantly contributes to the development of cohesive, clear, and comprehensible speech. Results: The research indicated that "Repetition," a lexical cohesive technique, and "Reference," a grammatical cohesive device, were extensively used by Oprah to reinforce her message to the audience. She used these two categories with the others to enhance the efficacy of her speech and its persuasive impact. Novelty: Oprah Winfrey is a credible individual, transcending her role as a media icon, which imparts considerable influence to her statements among millions. Oprah's extensive influence and media presence make her endorsements of politicians a significant effect in shaping voting patterns. Her support of Kamala Harris at the 2024 Democratic National Convention exemplifies the significant voter interest her speech garnered.